Design of transient protection systems : including supercapacitor based design approaches for surge protectors - Kularatna, Nihal; Steyn-Ross, Alistair; Fernando, Jayathu; James, Sisira (Elsevier, 2019)
Design of Transient Protection Systems: Including Supercapacitor Based Design Approaches for Surge Protectors is the only reference to consider surge protection for end-user equipment. This book fills the gap between academia and industry, presenting new product development approaches, such as the supercapacitor assisted surge absorber (SCASA) technique. It discusses protecting gear for modern electronic systems and consumer electronics, while also addressing the chain of design, development, implementation, recent theory and practice of developing transient surge protection systems. In addition, it considers all relevant technical aspects of testing commercial surge protectors, advances in surge protection products, components, and the abilities of commercial supercapacitors.